TECHNOLOGY OF DIGITAL ADAPTATION DATA OF MONETARY AND PENSION SUPPLY OF THE MILITARY PERSONNEL OF THE ARMED FORCES OF UKRAINE - Gorodianska, L. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The article explores the features of data generation in the system of monetary supply for the military personnel of the Armed Forces of Ukraine and the provision of administrative services related to pensions. A technology has been developed for digital adaptation of the initial data of the system of monetary supply for military personnel in accordance with the requirements for their archival storage, the needs for pensions and administrative services. It has been determined that the technology of digital adaptation of monetary supply data of the military personnel of the Armed Forces of Ukraine will provide an opportunity for digital transformation of personal account card data in accordance with the requirements for their archival storage. A mechanism has been formed for the receipt of monetary and pension data for a military serviceman of the Armed Forces of Ukraine in the personal account in the "Act" application. It has been established that the mechanism determines the features of the movement of digital data from the system of monetary supply of military units (institutions, organizations) to state institutions - the State Tax Service of Ukraine, the Pension Fund of Ukraine and the personal account of a serviceman in the "Act" application (administrative services). The interaction of the relevant electronic registers organized by the Ministry of Digital Transformation of Ukraine, in particular between the State Tax Service of Ukraine and the Pension Fund of Ukraine, is disclosed. The movement of monetary support data for the military personnel of the Armed Forces of Ukraine from the military unit (institution, organization) to state institutions, such as the State Tax Service of Ukraine, the Pension Fund of Ukraine and banking institutions, has been determined. It has been established that a feature of the provision of administrative services to a military serviceman is the organization of access to a personal account in the "Act" application.
Keywords: technology, digital adaptation of data, military servicemen's personal account cards, electronic registers, digital adaptation mechanism, financial security data, administrative services, pension provision, archival storage